Plasma Microbial Cell-free DNA Next-generation Sequencing in the Diagnosis and Management of Febrile Neutropenia - Benamu, Esther; Gajurel, Kiran; Anderson, Jill N; Lieb, Tullia; Gomez, Carlos A; Seng, Hon; Aquino, Romielle; Hollemon, Desiree; Hong, David K; Blauwkamp, Timothy A; Kertesz, Mickey; Blair, Lily; et al. (Clinical infectious diseases, 2022)
Abstract Background Standard testing fails to identify a pathogen in most patients with febrile neutropenia (FN). We evaluated the ability of the Karius microbial cell-free DNA sequencing test (KT) to identify infectious etiologies of FN and its impact on antimicrobial management. Methods This prospective study (ClinicalTrials.gov; NCT02912117) enrolled and analyzed 55 patients with FN. Up to 5 blood samples were collected per subject within 24 hours of fever onset (T1) and every 2 to 3 days. KT results were compared with blood culture (BC) and standard microbiological testing (SMT) results. Results Positive agreement was defined as KT identification of ≥1 isolate also detected by BC. At T1, positive and negative agreement were 90% (9/10) and 31% (14/45), respectively; 61% of KT detections were polymicrobial. Clinical adjudication by 3 independent infectious diseases specialists categorized Karius results as: unlikely to cause FN (N = 0); definite (N = 12): KT identified ≥1 organism also found by SMT within 7 days; probable (N = 19): KT result was compatible with a clinical diagnosis; possible (N = 10): KT result was consistent with infection but not considered a common cause of FN. Definite, probable, and possible cases were deemed true positives. Following adjudication, KT sensitivity and specificity were 85% (41/48) and 100% (14/14), respectively. Calculated time to diagnosis was generally shorter with KT (87%). Adjudicators determined real-time KT results could have allowed early optimization of antimicrobials in 47% of patients, by addition of antibacterials (20%) (mostly against anaerobes [12.7%]), antivirals (14.5%), and/or antifungals (3.6%); and antimicrobial narrowing in 27.3% of cases. Clinical Trials Registration NCT02912117 Conclusion KT shows promise in the diagnosis and treatment optimization of FN. Microbial cell-free DNA sequencing using the Karius test (KT) detects organisms not identified by conventional microbiological tests. KT can be useful in the etiologic diagnosis of infection of febrile neutropenia and may facilitate prompt and optimal antimicrobial therapy.